Phonological Change of Arabic and Dutch Loanwords in Indonesian - Arifuddin Balla (Institut Agama Islam Negeri Palopo, 2023)
In the literature of contact linguistics, phonology is known as the most affected by the contact. Long-standing situation and intense contact between Indonesian and Arabic and Dutch have led to extensive borrowed words yielding phonological change to accomodate foreign sounds that Indonesian inventory did not have. This article looks at the phonological change in Arabic and Dutch loanwords. Consonants from Arabic and Dutch are adapted into the closest consonants in Indonesian phonology while the consonant clusters are repaired by a vowel insertion. This study employed the descriptive qualitative method. The data are mainly from two dictionaries of Indonesian loanwords, Arabic Loanwords in Indonesian by Jones (1978) and Loanwords in Indonesian and Malay by Jones (2007). I also use my intuition as a native speaker of Indonesian to justify the lexicon items. The result of the analysis shows that there are four loan phonemes (/f/, /z/, /Êƒ/, and /x/) imported from Arabic and and phoneme /f/ from Dutch Dutch in the Indonesian phonological system. Â